2022
DOI: 10.1002/app.52697
|View full text |Cite
|
Sign up to set email alerts
|

Study on the polymerization process and monomer reactivity of EPEG‐type polycarboxylate superplasticizer

Abstract: In this study, the binary aqueous free radical copolymerization process of ethylene‐glycol monovinyl polyethylene glycol (EPEG) and acrylic acid (AA) was studied. The influence of monomer type and molar ratio on the conversion ratio of EPEG and the molar ratio of copolymer were investigated via gel permeation chromatography (GPC) by comparing the macromonomer molecular structures, side chain densities, and carboxyl group concentrations. According to the results, the reactivity of EPEG copolymerized with AA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Meanwhile, for the reaction monomers, in addition to some of the monomers introduced in the article, there are some new monomers that should also be applied in the reaction. For example, ether macromonomers from three‐carbon monomers to six‐carbon monomers have different reactivities due to the different electron cloud densities at one end of the double bond, which provides new monomer options for future reaction synthesis 48 . In addition, there are relatively few studies on gradient polycarboxylic acid dispersants, which provides a new idea for future academic research.…”
Section: Prospectmentioning
confidence: 99%
“…Meanwhile, for the reaction monomers, in addition to some of the monomers introduced in the article, there are some new monomers that should also be applied in the reaction. For example, ether macromonomers from three‐carbon monomers to six‐carbon monomers have different reactivities due to the different electron cloud densities at one end of the double bond, which provides new monomer options for future reaction synthesis 48 . In addition, there are relatively few studies on gradient polycarboxylic acid dispersants, which provides a new idea for future academic research.…”
Section: Prospectmentioning
confidence: 99%
“…From polyester macromonomers, it was gradually replaced by polyether macromonomers, including vinyl alcohol and vinyl ether macromonomers. , Among them, the unsaturated double bonds of vinyl ether macromonomers are directly connected to oxygen atoms, forming ether bonds in the molecular structure to compensate for the double bond electron cloud. Therefore, the reactivity of the double bond polymerization in vinyl ether macromonomers is stronger than that of ordinary macromonomers. , In our previous work, we investigated the effect of photoinitiated one-pot synthesis on the production of PCEs at different concentrations. The study revealed that the conversion rate and molecular weight of PCEs increase with the reaction concentration in the photoinitiation one-pot method.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Building‐gypsum system [ 15 ] and alkali‐activated system [ 16 ] were also studied. As an essential part of concrete components, the chemical structure of PCE also has an important impact on the working performance of concrete (setting‐time, [ 17 ] pumping performance, and rheological properties). The PCE also affects the crystal growth process and the microstructure [ 18 ] after hardening due to the complexation of COO − and Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Different rates of saponification in alkaline conditions lead to different rates of adsorption. [25] Mercapto chain transfer agents (such as 3-mercaptopropionic acid (3-MPA), [26] mercaptoacetic acid, [2] or mercaptoethanol [17] ) and non-mercapto chain transfer agents (such as sodium hypophosphate or sodium methallyl sulfonate [6] ) are commonly used in the industrial process of PCEs. However, the impact of these chain transfer agents on polymer structure and concrete slump retention has not been fully explored despite their crucial role in regulating the molecular weight of PCE.…”
Section: Introductionmentioning
confidence: 99%